Tafsir Era Digital di Indonesia: - Sihabussalam, Sihabussalam; Lailah, Sa’adatul; Wijaya, Roma (Lajnah Pentashihan Mushaf Al-Qur'an, 2024)
This paper examines how the influence of digital space on the development of contemporary interpretation gives rise to mediatisation and democratization of interpretation. This paper is qualitative research using Teun A. van Dijk’s theory of critical discourse analysis to reveal the discourse carried by online interpreters, a visual ethnographic approach to the four platforms, and historical analysis to see the origins of the democratization of online interpretation. This article finds that the development of digital interpretation is highly correlated with media and digital platform structures. The periodization of digital-era interpretation in Indonesia began in 2012 on the YouTube channel, a year after the Facebook platform became a medium of interpretation. In 2016, followed by websites, and in 2017, on Instagram. Tafsir of digital in Indonesia has a two-way openness and affects the practice of tafsir in general; namely, the loss of an integral part of tafsir and the discourse of Qur’anic Tafsir is increasingly globalized. Three discourses are presented in digital interpretation in Indonesia: thematization in the interpretation of the Qur’an, the internal and external capacity of mufasir, and the dominance of ideology and media.